Strong religion, zealous media : Christian fundamentalism and communication in India - Thomas, Pradip Ninan (Thousand Oaks : SAGE Publications, 2008)
"Strong Religion, Zealous Media: Christian Fundamentalism and Communication in India is the first in-depth cultural and social analysis of the growth of conservative forms of Christianity within the Protestant tradition in India and the many ways in which these new churches use the media. Arguing that Christian broadcasting needs to be seen as an essential aspect of a 'muscular' Christianity that has increasingly colonised globalising cities such as Chennai, the book concludes with a strong validation of multi-religious India and the need for a robust inter-faith media response to combat religious fundamentalism. This is a highly recommended reading for students, researchers and social scientists involved in religion and media issues, religion departments, seminaries, civil society involved in inter-faith issues and all those who are interested in exploring the politics of religion in the subcontinent."--BOOK JACKET
Introduction -- Section I: Locating the study -- Christian fundamentalism and other fundamentalisms -- Christian fundamentalism and the media -- Christianity in India -- Pentecostalism and neo-Pentecostalism : the global and the local -- Section II: Theory and concepts -- Bourdieu, Christianity, and mediated Christianity in India -- Section III: The cultural/media practices of Christian fundamentalism -- The changing nature of Christian broadcasting in India -- Cyber-contestations : Christian and Hindu fundamentalisms on the web -- Benny Hinn's festival of blessings : the analysis of a Christian crusade in India -- Section IV: Towards another religious communication -- Communication and the search for inter-subjective futures
Includes bibliographical references and index
Keywords: Fundamentalism -- India; Mass media in religion -- India; Communication -- India; Mass media -- India